simplify −2(j^2− k) − 6(j^2 + 3k )

Question

simplify
−2(j^2− k) − 6(j^2 + 3k )

in progress 0
King 4 weeks 2021-08-17T17:00:28+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-17T17:02:09+00:00

    Answer:-8j^2-16k

    Step-by-step explanation:

    First step:-2j^2-(-2)k=-2j^2+2k

    Second step:

    -6(j^2+3k) use the formula a(b+c)=ab + ac

    a=-6 b=j^2 c=3k

    -6j^2+(-6).3k

    -6j^2-6.3k=-6j^2-18k because we multiplied 6×3=18

    So we gather the whole equation And simplify

    -2j^2+2k-6j^2-18k

    -2j^2-6j^2 +2k-18k(add like terms)6+2=8

    -8j^2+2k-18K (subtract Like terms 18-2=16)

    And the answer will give -8j^2-16k

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )